2003
DOI: 10.1128/aem.69.7.4308-4311.2003
|View full text |Cite
|
Sign up to set email alerts
|

Use of Root Organ Cultures To Investigate the Interaction between Glomus intraradices and Pratylenchus coffeae

Abstract: The interaction between Glomus intraradices and Pratylenchus coffeae on transformed carrot roots was studied in root organ culture. G. intraradices provided the roots with increased protection against P. coffeae by suppressing nematode reproduction in the roots. The internal and external mycorrhizal development was not influenced by the presence of the nematodes.The effects of arbuscular mycorrhizal fungi (AMF) on damage caused by root nematodes have been widely addressed (2, 21, 23). However, most research so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 17 publications
3
11
1
Order By: Relevance
“…Such observation confirmed previous results obtained with in vitro cultures of various AM fungi [36,26]. Specifically focusing on G. intraradices , coefficients of variation calculated from different experiments ranked from 11%[37] to 22%[31], 38%[38] and even 61%[33]. The high variability observed in our experiment could be attributed to the host–fungus interaction and to both the fungal and plant physiology.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Such observation confirmed previous results obtained with in vitro cultures of various AM fungi [36,26]. Specifically focusing on G. intraradices , coefficients of variation calculated from different experiments ranked from 11%[37] to 22%[31], 38%[38] and even 61%[33]. The high variability observed in our experiment could be attributed to the host–fungus interaction and to both the fungal and plant physiology.…”
Section: Discussionsupporting
confidence: 91%
“…The length of extraradical hyphae measured in our study was similar to the values recorded in experiments conducted on excised transformed carrot roots with three different strains of G. intraradices [31,33]. Identically, the intraradical root colonization values estimated in our system were equivalent with the ones obtained on excised transformed carrot roots associated with G. intraradices , using the same method of estimation [33].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For example, it was shown that Radopholus similis and Pratylencus coffeae affected the frequency of Funneliformis mosseae colonization in banana, but not the intensity (Elsen et al, 2003a,b). In contrast, root colonization by R. irregularis in vitro banana plantlets was not affected either by R. similis (Koffi et al, 2013) or by P. coffeae in transformed carrot roots (Elsen et al, 2003c). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, AMF affects the nematodes by altering root exudates (Graham and Menge 1982) or by producing phytoalexins in the root, such as glyceollin, which could have nematicidal effects (Morandi 1996). Although possible mechanisms have been proposed to explain the reduction of harmful nematodes in the presence of AMF, they remain a matter of speculation (Elsen et al 2001;Elsen et al 2003). The interaction between the AMF and Meloidogyne spp.…”
Section: Introductionmentioning
confidence: 99%